Assessment of Selected Barangays in Makati City Towards Improved Barangay Governance - Rosalyn R. Flores (Indonesian Association for Public Administration (IAPA), 2019)
In international development as noted at the Wikipedia, good governance is a subjective term that describes how public institutions conduct public affairs and manage public resources in the preferred way. Governance is the process of decision – making and the process by which decisions are implemented or not. The term governance can apply to corporate, international, national, local governance or to the interactions between other sectors in the society. (1)